FAMILY DOLICHOPODIDAE - Capellari, Renato Soares (Zootaxa, 2016)
The Dolichopodidae recorded from Colombia are listed based on literature data only and currently comprise 30 species in 14 genera (six subfamilies). Information on type material and depository institutions is given.